PENGARUH REPUTASI AUDITOR DAN TIPE KEPEMILIKAN PERUSAHAAN PADA PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - I Dewa Made Mahayana; I Made Bagiada (P3M Politeknik Negeri Bali, 2015)
This study was to analyze the effect of auditor reputation and the ownership type of the company in voluntary disclosure by using data on the Indonesian stock exchange where the research object is the financial report that manufacturing companies listed on the Indonesia Stock Exchange. Based on the results of multiple regression analysis (multiple regression) with a confidence level of 95% (α = 5%), the coefficient of multiple correlation was found between the independent variables with the dependent variable 0.395 (R = 39.5%), this means that the level of the relationship between the independent variables the dependent variable is 39.50%. The coefficient of determination (R2 = 0.156), these results explain that 15.60% voluntary disclosure in annual reports listed manufacturing companies in the Stock Exchange, can be explained by the auditor reputation variables and variables of type of ownership, while 84.40% were explained by other variables outside of research. The results of multiple regression analysis on independent variables auditor reputation have significant value on the dependent variable 0,036 voluntary disclosure. These results show the higher the auditor's reputation higher voluntary disclosure, or conversely the lower the auditor reputation voluntary disclosure will be lower. Internal ownership has a significant value of 0.029, these results suggest that the independent variable is the significance of internal ownership is less than 0.05 (p <0.05), these results indicate that the higher the internal ownership, the higher the voluntary disclosure, or conversely the lower internal ownership of the company voluntary disclosure will also be lower. Ownership of government institutions, showed results lower than 0.022 significance level of 0.05 (P <0.05), these results suggest that the positive effect of government ownership on voluntary disclosure (voluntary disclousure). These test results show the higher holdings of government institutions, the company voluntary disclosure also higher, or conversely the lower ownership of government institutions, the voluntary disclosure will be lower, whereas non-governmental institutions ownership shows significant results 0,040 which was lower than the 0.05 level (P <0.05). , the ownership of institution non-governmental companies positive effect on voluntary disclosure (voluntary disclosure). Statistical tests above show that the higher the ownership of non-governmental institutions, the voluntary disclosure will be higher, and vice versa the lower the ownership of non-governmental institutions, the voluntary disclosure would be lower.